2008
DOI: 10.1021/cm7025448
|View full text |Cite
|
Sign up to set email alerts
|

Short-Range Structure of Proton-Conducting Perovskite BaInxZr1-xO3-x/2 (x = 0−0.75)

Abstract: In a systematic study we investigate the effect of dopant level and hydration on the short-range structure of the proton conducting perovskite-type oxide BaInxZr1−xO 3−x/2 (x = 0 − 0.75), using infrared and Raman spectroscopy. The results show that doping leads to significant local distortions of the average cubic structure of these materials. By increasing the In concentration from x = 0 to x = 0.75 new bands appear and grow in intensity in both the IR and Raman spectra, showing that the local distortions bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
101
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(113 citation statements)
references
References 48 publications
11
101
0
1
Order By: Relevance
“…Hydrated samples were prepared by annealing the powder samples at 275-300°C under a flow of Ar saturated with water vapor for 10 days. Further details of the sample preparation procedure can be found elsewhere [3].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hydrated samples were prepared by annealing the powder samples at 275-300°C under a flow of Ar saturated with water vapor for 10 days. Further details of the sample preparation procedure can be found elsewhere [3].…”
Section: Methodsmentioning
confidence: 99%
“…In a previous work we investigated the short-range structure of the proton-conducting BaIn x Zr 1 − x O 3 − x/2 (x = 0, 0.10, 0.25, 0.375, 0.50, 0.625 and 0.75) perovskite series, using infrared (IR) and Raman spectroscopy [3].That study showed that the doping with In onto the B site of the perovskite leads to significant local distortions of the average cubic structure, that the distortions become more pronounced with increasing In concentration, and that they are largely uncorrelated to the presence of oxygen vacancies [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to keep the charge balance, oxygen leaves the structure, forming vacancies. Special cases of the acceptor-doped perovskites are the brownmillerite-structured oxides, such as Ba 2 In 2 O 5 , where B 4+ ions are completely substituted by lower-valent metal ions, M 3+ [10,11,15]. At lower temperatures (e.g., up to 925 • C for Ba 2 In 2 O 5 ) the oxygen vacancies are ordered in parallel tetrahedral oxygen vacancy layers, alternating with octahedral perovskite layers [16].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] In these materials, the ideal perovskite A 2+ B 4+ O 3 2− is doped with lower-valent M 3+ ions, forming oxygen vacancies to compensate for the charge difference. 4 Existence of the oxygen vacancies favors oxygen ion transport and causes oxygen ion conduction in these materials. Moreover, mixed oxygen-ion and proton conduction has been found in these systems, with oxygen ion conduction predominant at high temperatures ͑typi-cally above 500°C͒ and protonic conduction predominant at low temperatures ͑typically below 500°C͒.…”
mentioning
confidence: 99%